Keynote address at the 7th National Agronomists’ Workshop 2011 - Paudel, MN (Agronomy Journal of Nepal, 2013)
7th National Agronomists’ Workshop 2011, Chaitra 14-15, 2067 (March 28-29, 2011), Jointly organized by : Crop Development Directorate (CDD), Department of Agriculture (DoA) and Agronomy Society of Nepal (ASoN). Theme : Agronomy for food and seed security. Venue : Training Hall DoA, Hariharbhawan.